Polylactic acid composition capable of being subjected to household composting degradation and preparation method of polylactic acid composition
By introducing the Co-zeolite imidazole ester skeleton and diatom shell complex in polylactic acid, combined with the photocatalytic action of nanotitanium dioxide, the problem of slow degradation of polylactic acid is solved and the rapid degradation of polylactic acid is achieved.
Patent Information
- Application Number
- CN202411652797.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The degradation rate of polylactic acid is slow, mainly due to its tight structure and water is not easy to penetrate, resulting in a slow hydrolysis process.
Using polylactic acid compositions, including polylactic acid, polyhydroxy fatty acid esters, diatom shell complexes loaded with Co-zeolite imidazole skeletons and nanotitanium dioxide, the hydroxyl group is activated by reacting the Co-zeolite imidazole skeleton with methanol, and the diatom shell promotes Dispersion and heterogeneous erosion degradation, nanotitanium dioxide accelerates degradation through photocatalysis.
The degradation rate of polylactic acid is significantly improved. Through the synergistic action of the Co-zeolite imidazole ester framework, diatom shell and nanotitanium dioxide, the cracking and degradation of polylactic acid is promoted, and the degradation time is significantly shortened.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of environmentally friendly degradable polymers, and more specifically, to a polylactic acid composition that can be degraded by household composting and a preparation method thereof. Background Art
[0002] Since its invention, plastic has rapidly developed into one of the most widely used materials in the world, but most plastics cannot be naturally degraded after being discarded, which has brought great challenges to the ecological environment. Degradable polymer materials are a type of green and environmentally friendly materials that are expected to replace traditional fossil-based plastics. Among them, polylactic acid has good processing performance and biocompatibility, becoming one of the most representative and promising degradable materials.
[0003] The main principle of PLA degradation is that under the action of hydrolysis reaction, the ester group in the PLA structure will break, causing the overall structure of PLA to crack, allowing microorganisms to enter the interior of the PLA tissue, and then the microorganisms will degrade the remaining PLA short chains and finally degrade them into water and carbon dioxide.
[0004] However, due to the tight overall structure of polylactic acid, the long chains of polylactic acid molecules have a regular arrangement structure under the intermolecular dipole force, which makes it difficult for water to penetrate into the interior of the polylactic acid tissue, thereby slowing down the hydrolysis process of polylactic acid, resulting in the defect that conventional polylactic acid has a long degradation time. Summary of the invention
[0005] In order to improve the defect of conventional polylactic acid having a long degradation rate, the present application provides a polylactic acid composition that can be degraded by home composting and a preparation method thereof.
[0006] In the first aspect, the present application provides a polylactic acid composition that can be degraded by household composting, using the following technical solution: A polylactic acid composition that can be degraded by household composting comprises the following raw materials in parts by weight: 60-70 parts of polylactic acid, 10-20 parts of polyhydroxyalkanoate, 8-12 parts of diatom frustule complex and 2-4 parts of compatibilizer; The diatom frustule complex is loaded with a Co-based zeolite imidazolate framework.
[0007] The Co-based zeolite imidazolate skeleton can promote the degradation of polylactic acid in a methanol environment. The mechanism is that polylactic acid can react on the surface of the Co-based zeolite imidazolate skeleton, where the carbonyl oxygen is activated by the Lewis acid in the Co-based zeolite imidazolate skeleton, making it easier to react with methanol. At the same time, the Lewis base on the Co-based zeolite imidazolate skeleton activates the oxygen atom on the hydroxyl group in methanol, enhancing its nucleophilicity, which is more conducive to attacking the ester group in polylactic acid to form a new CO bond, breaking the original CO bond, thereby cracking the polylactic acid to generate short-chain oligomers, and then degrading through further alcoholysis.
[0008] However, the Co-based zeolite imidazolate skeleton has poor dispersibility in polylactic acid, which results in insufficient degradation-promoting effect of the Co-based zeolite imidazolate skeleton on polylactic acid. Diatom frustules have a unique porous structure, so the Co-based zeolite imidazolate skeleton can be loaded on the diatom frustules. At the same time, the surface of the diatom frustules contains a large number of silanol groups, so the diatom frustules can drive the Co-based zeolite imidazolate skeleton to be evenly dispersed in the polylactic acid matrix.
[0009] In addition, diatom shells can also promote the heterogeneous erosion and degradation of polylactic acid, regulate the degradation order of the crystalline and amorphous regions of polylactic acid, and accelerate the degradation of the crystalline region. The mechanism is speculated that the stress intensity factor of the microfibril crystal end induced by diatom shells far exceeds the fracture toughness of polylactic acid, resulting in unstable crack expansion, further accelerating water absorption and cracking, and in coordination with the alcoholysis of the Co-based zeolite imidazole ester skeleton, further improving the degradation rate of polylactic acid.
[0010] However, the addition of diatom frustule complexes will significantly reduce the mechanical properties of the polylactic acid matrix. Therefore, polyhydroxyalkanoates are needed to form alloys to compensate for this, and compatibilizers can promote a more uniform distribution of polyhydroxyalkanoates and polylactic acid.
[0011] Preferably, the method for preparing the diatom frustule complex comprises the following steps: S1. Dispersing diatom frustules in PVP-methanol solution, stirring continuously for 10-14 hours to obtain diatom frustule dispersion; S2. Mix the diatom frustule dispersion with methanol, then add cobalt nitrate hexahydrate-ethanol solution and dimethylimidazole-methanol solution in sequence, react at room temperature for 10-14 hours, and finally wash and dry to obtain a diatom frustule complex.
[0012] Preferably, in the diatom frustule dispersion, the mass ratio of the diatom frustules, PVP and methanol is 0.1: (0.4-0.6): (10-16); In S2, the mass ratio of diatom frustule dispersion to methanol is (0.4-0.6): (0.4-0.6); In the cobalt nitrate hexahydrate-ethanol solution, the mass ratio of cobalt nitrate hexahydrate to ethanol is (0.01-0.02): (2-4); In the dimethylimidazole-methanol solution, the mass ratio of dimethylimidazole to methanol is (0.3-0.4): (4-6); The mass ratio of the diatom shell, cobalt nitrate hexahydrate and dimethylimidazole is: 0.1: (0.01-0.02): (0.3-0.4).
[0013] Preferably, the preparation method of the diatom frustules is: oxidizing the diatom with a 30% aqueous hydrogen peroxide solution for 10-14 hours, then placing it in a 1 mol / L hydrochloric acid solution for acidification for 20-30 hours, then washing it with water 4-6 times, and then sintering it at 500-700°C for 2-4 hours in an oxygen atmosphere, and finally grinding it to 400-600 mesh to obtain the diatom frustules.
[0014] Preferably, the diatom frustule complex is also loaded with nano-titanium dioxide.
[0015] Nano-titanium dioxide can promote the degradation of polyhydroxyalkanoates through photocatalysis. After photocatalytic cracking, polyhydroxyalkanoates can make the polylactic acid matrix structure in the alloy state amorphous, thereby forming a large number of voids and cracks. In the above process, water, alcohol and microorganisms enter the interior of the polylactic acid through the voids and cracks, thereby further accelerating the degradation of the polylactic acid.
[0016] Preferably, the surface of the nano-titanium dioxide is modified by a ruthenium-porphyrin complex.
[0017] The absorption wavelength of titanium dioxide is generally below 400nm, mainly ultraviolet light, but the ultraviolet light penetration is poor. When sunlight penetrates the atmosphere, most of the ultraviolet light is absorbed by the gaps. When the surface of nano-titanium dioxide is modified by ruthenium-porphyrin complex, nano-titanium dioxide can obtain a larger absorption range, thereby further accelerating the degradation of polylactic acid.
[0018] Specifically, the ruthenium-porphyrin complex has a large conjugated structure with multiple aromatic rings, which can transfer electrons and energy with nano-titanium dioxide particles, thereby further improving the photocatalytic performance of nano-titanium dioxide. In addition, after the ruthenium-porphyrin complex absorbs photons, it can produce singlet oxygen, and the singlet oxygen can play a role in oxidizing polyhydroxyalkanoates and polylactic acid, thereby further promoting the cracking of polyhydroxyalkanoates and the degradation of polylactic acid. Moreover, the ruthenium-porphyrin complex can also utilize the heavy atom effect of metal atoms to promote intersystem crossing of electrons in high-energy states, thereby increasing the yield of singlet oxygen and further promoting the degradation of polylactic acid.
[0019] Preferably, the modification method of the nano-titanium dioxide is: dispersing the nano-titanium dioxide in ethanol at a mass ratio of 1: (10-20), then adding ruthenium-porphyrin complex with a mass of 2-4% of the nano-titanium dioxide and continuously stirring, then centrifuging to remove the supernatant, and finally washing and drying to obtain nano-titanium dioxide with the surface modified by ruthenium-porphyrin complex.
[0020] Preferably, the mass ratio of the diatom shell to nano-titanium dioxide is 0.1:(0.04-0.06).
[0021] When the diatom shells and titanium dioxide adopt the above mass ratio, the prepared polylactic acid composition will have a better degradation effect.
[0022] In a second aspect, the present application provides a method for preparing a polylactic acid composition that can be degraded by home composting, using the following technical solution: A method for preparing a polylactic acid composition that can be degraded by home composting comprises the following steps: Step 1: mixing polylactic acid, polyhydroxyalkanoate and a compatibilizer, and then heating to 160-190° C. to melt them, to obtain a polylactic acid composition base material; Step 2: Cool the polylactic acid composition base material to 140-160°C, then add the diatom shell complex, mix evenly, and extrude and mold through a screw extruder. The screw extruder: the first melting section temperature is 145-152°C, the second melting section is 153-159°C, the third melting section is 132-139°C, the screw speed is 60-100rpm, and the extrusion port temperature is 118-122°C.
[0023] In summary, this application has the following beneficial effects: 1. The Co-based zeolite imidazolate skeleton can promote the degradation of polylactic acid in a methanol environment. The mechanism is that polylactic acid can react on the surface of the Co-based zeolite imidazolate skeleton, where the carbonyl oxygen is activated by the Lewis acid in the Co-based zeolite imidazolate skeleton, making it easier to react with methanol. At the same time, the Lewis base on the Co-based zeolite imidazolate skeleton activates the oxygen atom on the hydroxyl group in methanol, enhancing its nucleophilicity, which is more conducive to attacking the ester group in polylactic acid to form a new CO bond, breaking the original CO bond, thereby cracking the polylactic acid to generate short-chain oligomers, and then degrading through further alcoholysis.
[0024] 2. The Co-based zeolite imidazolate skeleton has poor dispersibility in polylactic acid, which results in insufficient degradation-promoting effect of the Co-based zeolite imidazolate skeleton on polylactic acid. Diatom frustules have a unique porous structure, so the Co-based zeolite imidazolate skeleton can be loaded on the diatom frustules. At the same time, the surface of the diatom frustules contains a large number of silanol groups, so the diatom frustules can drive the Co-based zeolite imidazolate skeleton to be uniformly dispersed in the polylactic acid matrix; In addition, diatom shells can also promote the heterogeneous erosion and degradation of polylactic acid, regulate the degradation order of the crystalline and amorphous regions of polylactic acid, and accelerate the degradation of the crystalline region. The mechanism is speculated that the stress intensity factor of the microfibril crystal end induced by diatom shells far exceeds the fracture toughness of polylactic acid, resulting in unstable crack expansion, further accelerating water absorption and cracking, and in coordination with the alcoholysis of the Co-based zeolite imidazole ester skeleton, further improving the degradation rate of polylactic acid.
[0025] Nano-titanium dioxide can promote the degradation of polyhydroxyalkanoates through photocatalysis. After photocatalytic cracking, polyhydroxyalkanoates can make the polylactic acid matrix structure in the alloy state amorphous, thereby forming a large number of voids and cracks. In the above process, water, alcohol and microorganisms enter the interior of the polylactic acid through the voids and cracks, thereby further accelerating the degradation of the polylactic acid.
[0026] The absorption wavelength of titanium dioxide is generally below 400nm, mainly ultraviolet light, but the ultraviolet light penetration is poor. When sunlight penetrates the atmosphere, most of the ultraviolet light is absorbed by the gaps. When the surface of nano-titanium dioxide is modified by ruthenium-porphyrin complex, nano-titanium dioxide can obtain a larger absorption range, thereby further accelerating the degradation of polylactic acid. DETAILED DESCRIPTION
[0027] The present application is further described in detail below in conjunction with Examples 1-5 and Comparative Examples 1-2.
[0028] raw material Polylactic acid Thailand Total L30; compatibilizer maleic anhydride grafted polypropylene Hongju Chemical; polyhydroxyalkanoate Dongguan Shenghao Plastic; PVP CAS: 9003-39-8; methanol CAS: 67-56-1; cobalt nitrate hexahydrate CAS: 10026-22-9; ethanol CAS: 64-17-5; dimethylimidazole CAS: 693-98-1; diatom boat-shaped algae self-cultivation; hydrogen peroxide CAS: 7722-84-1; hydrochloric acid CAS: 7647-01-0; nano titanium dioxide Yuxing R878; ruthenium-porphyrin complex preparation method, see application number 200610124361.2-Ruthenium porphyrin complex and its preparation method and application as a photosensitizer for photodynamic therapy specific implementation method 1-2 paragraph 1 first product.
[0029] Example Example 1 A polylactic acid composition capable of being degraded by household composting comprises the following raw materials: 65g of polylactic acid, 15g of polyhydroxyalkanoate, 10g of diatom frustule complex and 3g of compatibilizer-maleic anhydride grafted polypropylene.
[0030] The diatom frustule complex is loaded with a Co-based zeolite imidazolate skeleton, and the preparation method of the diatom frustule complex comprises the following steps: S1, dispersing diatom frustules in PVP-methanol solution, stirring continuously for 12 hours to obtain diatom frustule dispersion; S2. Mix the diatom frustule dispersion with methanol, then add cobalt nitrate hexahydrate-ethanol solution and dimethylimidazole-methanol solution in sequence, react at room temperature for 12 hours, and finally wash and dry to obtain a diatom frustule complex.
[0031] Among them, in the diatom frustule dispersion, the mass ratio of diatom frustule, PVP and methanol is 0.1:0.5:14; In S2, the mass ratio of diatom frustule dispersion to methanol is 0.4:0.6; In the cobalt nitrate hexahydrate-ethanol solution, the mass ratio of cobalt nitrate hexahydrate to ethanol is 0.0175:3; In the dimethylimidazole-methanol solution, the mass ratio of dimethylimidazole to methanol is 0.35:5; The mass ratio of diatom shells, cobalt nitrate hexahydrate and dimethylimidazole is 0.1:0.0175:0.35.
[0032] The preparation method of diatom shells is as follows: oxidize the diatoms with a 30% hydrogen peroxide aqueous solution for 12 hours, then place them in a 1 mol / L hydrochloric acid solution for acidification for 24 hours, then wash them with water 5 times, and then sinter them at 600°C for 3 hours in an oxygen atmosphere, and finally grind them to 500 mesh to obtain diatom shells.
[0033] Example 2 The difference between Example 2 and Example 1 is that nano-titanium dioxide is loaded in the diatom frustule complex.
[0034] The method for preparing the diatom frustule complex comprises the following steps: S1, dispersing diatom frustules and nano-titanium dioxide in PVP-methanol solution, stirring continuously for 12 hours to obtain a diatom frustule dispersion; S2. Mix the diatom frustule dispersion with methanol, then add cobalt nitrate hexahydrate-ethanol solution and dimethylimidazole-methanol solution in sequence, react at room temperature for 12 hours, and finally wash and dry to obtain a diatom frustule complex.
[0035] Among them, in the diatom frustule dispersion, the mass ratio of diatom frustule, nano-titanium dioxide, PVP and methanol is 0.1:0.05:0.5:14; In S2, the mass ratio of diatom frustule dispersion to methanol is 0.4:0.6; In the cobalt nitrate hexahydrate-ethanol solution, the mass ratio of cobalt nitrate hexahydrate to ethanol is 0.0175:3; In the dimethylimidazole-methanol solution, the mass ratio of dimethylimidazole to methanol is 0.35:5; The mass ratio of diatom shells, cobalt nitrate hexahydrate and dimethylimidazole is 0.1:0.0175:0.35.
[0036] Example 3 The difference between Example 3 and Example 2 is that the surface of the nano-titanium dioxide is modified by a ruthenium-porphyrin complex.
[0037] The modification method of nano-titanium dioxide is as follows: disperse the nano-titanium dioxide in ethanol at a mass ratio of 1:15, then add ruthenium-porphyrin complex with a mass of 3% of the nano-titanium dioxide and continue stirring, then centrifuge to remove the supernatant, and finally wash and dry to obtain nano-titanium dioxide with the surface modified by ruthenium-porphyrin complex.
[0038] Embodiment 4-5 The difference between Example 4-5 and Example 3 is that the mass ratios of diatom frustules, nano-titanium dioxide, cobalt nitrate hexahydrate and dimethylimidazole are different, as shown in Table 1.
[0039] Table 1 Mass ratio of some components of the diatom frustule complex in Examples 3-5 Example 3 Example 4 Example 5 Diatom frustules 0.1 0.1 0.1 Nano Titanium Dioxide 0.05 0.04 0.06 Cobalt nitrate hexahydrate 0.0175 0.01 0.02 dimethylimidazole 0.35 0.4 0.3 Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no diatom frustule complex is added.
[0040] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the diatom frustule complex is replaced with the same added amount of Co-based zeolite imidazolate framework.
[0041] Performance testing Detection Methods 1. Degradation effect test Three samples were taken from Examples 1-5 and Comparative Examples 1-2, and then the site was arranged according to the method in GB / T18006.2-1999. The samples were made into 16 cm 2 The samples, 5 mm thick, were subjected to conventional household composting and sprayed with methanol at the same time. The sample status was observed daily, and the time when the sample fragmentation area reached 50% was recorded and the average value was taken.
[0042] The test data are shown in Table 2.
[0043] Table 2 Test data table of Examples 1-5 and Comparative Examples 1-2 Fragmentation days / day Fragmentation days / day Example 1 63 days Example 5 46 days Example 2 50 days Comparative Example 1 >150 days Example 3 42 days Comparative Example 2 84 days Example 4 44 days Referring to Comparative Examples 1 and 2 and in combination with Table 2, it can be seen that the fragmentation days of Comparative Example 2 are significantly reduced compared with Comparative Example 1, which indicates that the addition of the Co-based zeolite imidazolate skeleton can significantly increase the degradation rate of polylactic acid.
[0044] The reason is that the Co-based zeolite imidazolate skeleton can promote the degradation of polylactic acid in a methanol environment. The mechanism is that polylactic acid can react on the surface of the Co-based zeolite imidazolate skeleton, where the carbonyl oxygen is activated by the Lewis acid in the Co-based zeolite imidazolate skeleton, making it easier to react with methanol. At the same time, the Lewis base on the Co-based zeolite imidazolate skeleton activates the oxygen atom on the hydroxyl group in methanol, enhancing its nucleophilicity, which is more conducive to attacking the ester group in polylactic acid to form a new CO bond, breaking the original CO bond, thereby cracking the polylactic acid to generate short-chain oligomers, and then degrading through further alcoholysis.
[0045] Referring to Example 1 and Comparative Example 2 and in combination with Table 2, it can be seen that, relative to Comparative Example 2, the number of days for fragmentation in Example 1 is further reduced, which indicates that the provision of the diatom frustule complex can further increase the degradation rate of polylactic acid.
[0046] The reason is that the Co-based zeolite imidazolate skeleton has poor dispersibility in polylactic acid, which leads to insufficient effect of the Co-based zeolite imidazolate skeleton in promoting the degradation of polylactic acid. Diatom frustum has a unique porous structure, so the Co-based zeolite imidazolate skeleton can be loaded on the diatom frustum. At the same time, the surface of the diatom frustum contains a large number of silanol groups, so the diatom frustum can drive the Co-based zeolite imidazolate skeleton to be evenly dispersed in the polylactic acid matrix.
[0047] In addition, diatom shells can also promote the heterogeneous erosion and degradation of polylactic acid, regulate the degradation order of the crystalline and amorphous regions of polylactic acid, and accelerate the degradation of the crystalline region. The mechanism is speculated that the stress intensity factor of the microfibril crystal end induced by diatom shells far exceeds the fracture toughness of polylactic acid, resulting in unstable crack expansion, further accelerating water absorption and cracking, and in coordination with the alcoholysis of the Co-based zeolite imidazole ester skeleton, further improving the degradation rate of polylactic acid.
[0048] Referring to Example 1 and Example 2 and combining with Table 2, it can be seen that compared with Example 1, the fragmentation days of Example 2 are further reduced, which shows that the addition of nano-titanium dioxide can further increase the degradation rate of polylactic acid.
[0049] The reason is that nano-titanium dioxide can promote the degradation of polyhydroxyalkanoates through photocatalysis, and after photocatalytic cracking, polyhydroxyalkanoates can make the polylactic acid matrix structure in the alloy state amorphous, thereby forming a large number of voids and cracks. In the above process, water, alcohol and microorganisms enter the interior of the polylactic acid through the voids and cracks, thereby further accelerating the degradation of the polylactic acid.
[0050] Referring to Example 2 and Example 3 and combining with Table 2, it can be seen that compared with Example 2, the number of days for fragmentation in Example 3 is further reduced, which shows that after the surface of nano-titanium dioxide is modified by ruthenium-porphyrin complex, the degradation rate of polylactic acid can be further improved.
[0051] The reason is that the absorption wavelength of titanium dioxide is generally below 400nm, mainly ultraviolet light, but the ultraviolet light penetration is poor. When sunlight penetrates the atmosphere, most of the ultraviolet light is absorbed by the gaps. When the surface of nano-titanium dioxide is modified by ruthenium-porphyrin complex, nano-titanium dioxide can obtain a larger absorption range, thereby further accelerating the degradation of polylactic acid.
[0052] Specifically, the ruthenium-porphyrin complex has a large conjugated structure with multiple aromatic rings, which can transfer electrons and energy with nano-titanium dioxide particles, thereby further improving the photocatalytic performance of nano-titanium dioxide. In addition, after the ruthenium-porphyrin complex absorbs photons, it can produce singlet oxygen, and the singlet oxygen can play a role in oxidizing polyhydroxyalkanoates and polylactic acid, thereby further promoting the cracking of polyhydroxyalkanoates and the degradation of polylactic acid. Moreover, the ruthenium-porphyrin complex can also utilize the heavy atom effect of metal atoms to promote intersystem crossing of electrons in high-energy states, thereby increasing the yield of singlet oxygen and further promoting the degradation of polylactic acid.
[0053] Referring to Examples 3-5 and in combination with Table 2, it can be seen that, relative to Example 3, the fragmentation days of Examples 4-5 are relatively longer, which indicates that when the mass proportions of diatom frustules, nano-titanium dioxide, cobalt nitrate hexahydrate and dimethylimidazole are adopted in Example 3, the prepared diatom frustule complex can promote polylactic acid to have a better degradation effect.
[0054] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A polylactic acid composition that can be degraded by home composting, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of polylactic acid, 10-20 parts of polyhydroxyalkanoate, 8-12 parts of diatom frustule complex and 2-4 parts of compatibilizer; the diatom frustule complex is loaded with a Co-based zeolite imidazole ester skeleton.
2. The home compostable polylactic acid composition according to claim 1, characterized in that: The method for preparing the diatom frustule complex comprises the following steps: S1. Dispersing diatom frustules in PVP-methanol solution, stirring continuously for 10-14 hours to obtain diatom frustule dispersion; S2. Mix the diatom frustule dispersion with methanol, then add cobalt nitrate hexahydrate-ethanol solution and dimethylimidazole-methanol solution in sequence, react at room temperature for 10-14 hours, and finally wash and dry to obtain a diatom frustule complex.
3. The home compostable polylactic acid composition according to claim 2, characterized in that: In the diatom frustule dispersion, the mass ratio of the diatom frustule, PVP and methanol is 0.1: (0.4-0.6): (10-16); In S2, the mass ratio of diatom frustule dispersion to methanol is (0.4-0.6): (0.4-0.6); In the cobalt nitrate hexahydrate-ethanol solution, the mass ratio of cobalt nitrate hexahydrate to ethanol is (0.01-0.02): (2-4); In the dimethylimidazole-methanol solution, the mass ratio of dimethylimidazole to methanol is (0.3-0.4): (4-6); The mass ratio of the diatom shell, cobalt nitrate hexahydrate and dimethylimidazole is: 0.1:(0.01-0.02):(0.3-0.4)。 4. The home compostable polylactic acid composition according to claim 3, characterized in that: The preparation method of the diatom shell is as follows: oxidizing the diatom with a 30% hydrogen peroxide aqueous solution for 10-14 hours, then placing it in a 1 mol / L hydrochloric acid solution for acidification for 20-30 hours, then washing it with water for 4-6 times, and then sintering it at 500-700° C. for 2-4 hours in an oxygen atmosphere, and finally grinding it to 400-600 meshes to obtain the diatom shell.
5. The home compostable polylactic acid composition according to claim 1, characterized in that: The diatom frustule complex is also loaded with nano-titanium dioxide.
6. The home compostable polylactic acid composition according to claim 5, characterized in that: The surface of the nano titanium dioxide is modified by a ruthenium-porphyrin complex.
7. The home compostable polylactic acid composition according to claim 6, characterized in that: The modification method of the nano titanium dioxide is as follows: the nano titanium dioxide is dispersed in ethanol at a mass ratio of 1: (10-20), then a ruthenium-porphyrin complex is added with a mass ratio of 2-4% of the nano titanium dioxide and stirred continuously, then the supernatant is removed by centrifugation, and finally the nano titanium dioxide surface is washed and dried to obtain the nano titanium dioxide with the surface modified by the ruthenium-porphyrin complex.
8. The home compostable polylactic acid composition according to claim 5, characterized in that: The mass ratio of the diatom shell to the nano-titanium dioxide is 0.1:(0.04-0.06).
9. A method for preparing a home compostable polylactic acid composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: mixing polylactic acid, polyhydroxyalkanoate and a compatibilizer, and then heating to 160-190° C. to melt them, to obtain a polylactic acid composition base material; Step 2: Cool the polylactic acid composition base material to 140-160°C, then add the diatom shell complex, mix evenly, and extrude and mold through a screw extruder. The screw extruder: the first melting section temperature is 145-152°C, the second melting section is 153-159°C, the third melting section is 132-139°C, the screw speed is 60-100rpm, and the extrusion port temperature is 118-122°C.
Citation Information
Patent Citations
High-strength biodegradable plastic and preparation method thereof
CN114316542A
Seedling raising cup capable of being used for household compost degradation
CN118359909A
Polylactic acid-polyhydroxyalkanoate-based degradable composite material and preparation method thereof
CN118459958A